Correlation between vitamin A, D, E, and K levels in children with allergic rhinitis: a propensity-matched analysis - Huanjun Luo; Xiaowei Wang; Haibo Kong; Jing Wang; Qin Zhou (BMC Pediatrics)
Abstract Background The effect of vitamins on children with allergic rhinitis (AR) has been controversial. The correlation between the serum levels of vitamins A, D, E, and K and AR in children needs to be explored. Methods Two hundred and eight children with AR (experimental group) and 239 healthy children (control group) were randomly selected from the Pediatric Clinic of Zhejiang Provincial People's Hospital between January 2021 and October 2023. Blood samples were drawn to measure the levels of vitamins A, D, E, and K. Five baseline parameters (gender, age, height, weight, and BMI) were measured in the two sets of data for the propensity score and were matched in a 1:1 ratio to obtain 180 groups. Results The serum vitamin A [Md (IQR):359.50 (295.06,415.26)ng/mL] content of children in the AR group was generally lower than that in the control group, and the serum vitamin K [Md (IQR):0.75 (0.4,1.19)ng/mL] content was generally higher than that in the control group. The differences between the two groups with respect to the levels of vitamins A and K were statistically significant (P < 0.05). In contrast, the differences in the levels of vitamins D and E between the two groups were not statistically significant (P > 0.05). The levels of vitamins A, D, E, and K in both groups were within normal ranges. Conclusion The vitamin A content in children with AR was lower than that in the control group, whereas the vitamin K content was higher. The correlation between the levels of vitamins D and E and AR in children needs further investigation.